Bioethics and Medical Ethics in Countries of Central and Eastern Europe. An Introduction - Banse, Gerhard; Bartíková, Monika; Kiepas, Andrzej; Dumitrascu, Dan L.; Kovaľová, Daniela; Kuře, Josef; Birnbacher, Dieter; Friele, Minou Bernadette; Bogner, Alexander (Teorie vědy / Theory of Science, 2019)
The area of biomedicine is one of the fastest developing areas of science and technology. The perception of its possible and expected positive or negative impacts results in the growing number of bioethical discussions in scientific community, politics and public. Their intensity, focus and used methods differ from country to country. Th e authors of the prologue have tried to map the state of the art and expected development of bioethical discussion in the countries of Middle and Eastern Europe. In the beginning, they addressed the bioethical experts with short questionnaire from 7 “new” European countries (Croatia, Czech Republic, Hungary, Poland, Romania, Slovakia and Slovenia) and two “old” European countries (Germany and Austria). In the end, seven experts have responded their questions (Czech Republic, Poland, Romania, Slovakia, Austria and Germany) and expressed their expectations and difficulties of the development of bioethical discussions and institutionalisations in their countries. The authors summarize in the prologue the most interesting results.